1998
DOI: 10.1097/00005768-199812000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The gender difference in distance running performance has plateaued: an analysis of world rankings from 1980 to 1996

Abstract: Based on worldwide indices of competitive distance running, the gender difference in distance running performance has plateaued in recent years. Concomitantly, over the past decade, opportunities for women to train and compete have approached parity with those of men. It is likely that the current gender difference in performance will remain fairly constant because of biological differences between men and women that give men an advantage in distance running.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 7 publications
12
95
0
3
Order By: Relevance
“…[49,50] Interestingly, Speechly et al [51] reported that females, who were matched with males for a 42-km run, were faster than males in a 90-km race. Similarly, it has been shown that females and males who were matched for 50-km trail running performance also performed similarly in trail runs of 80-and 161-km distances.…”
Section: Sex Differences In Triathlon Performancementioning
confidence: 99%
See 1 more Smart Citation
“…[49,50] Interestingly, Speechly et al [51] reported that females, who were matched with males for a 42-km run, were faster than males in a 90-km race. Similarly, it has been shown that females and males who were matched for 50-km trail running performance also performed similarly in trail runs of 80-and 161-km distances.…”
Section: Sex Differences In Triathlon Performancementioning
confidence: 99%
“…[52] Despite the suggestion in 1992 that females may one day outrun males in competitive ultra-endurance events [53] , elite males appear to run approximately 10-12% faster than elite females across all endurance running race distances up to marathon, with the sex difference narrowing as the race distance increases. [49,50] However, at distances greater than 100km, such as the 161-km ultramarathon, the difference seems even larger, with females 20-30% slower than males. [49,54,55] Insert TABLE 1…”
Section: Sex Differences In Triathlon Performancementioning
confidence: 99%
“…Although some authors have questioned whether the gap in gender difference in endurance performance could be closed (Bam, Noakes, Juritz, & Dennis, 1997;Coast, Blevins, & Wilson, 2004;Whipp, & Ward 1992), more recent studies could not confirm this assumption showing that the gender difference in both endurance performance (Cheuvront, Carter, DeRuisseau, & Moffart, 2005;Sparling, O'Donnell, & Snow, 1998) and anaerobic sprints (Seiler, De Koning, & Foster, 2007) is no longer diminishing. Coast et al (2004) for example analysed the gender difference in running performances at distances from 100 m to 200 km.…”
Section: Introductionmentioning
confidence: 99%
“…For HC, the sex difference showed rather large fluctuations across the years but remained greater than 25% for the top three athletes. These values are much greater compared with traditional values around 10-12% reported in the literature for able-bodied runners (Hunter, et al 2011;Lepers & Cattagni, 2012;Sparkling, O'Donnell & Snow, 1998). Coutts and Schutz (1988) have reported that sex differences in performance were 15% for 200 m and 23% for the 5000 m track, respectively.…”
Section: Sex Difference In Performancementioning
confidence: 73%